Temporal dynamics of cerebral blood flow during the first year after moderate-severe traumatic brain injury: A longitudinal perfusion MRI study - Gaggi, Naomi L.; Ware, Jeffrey B.; Dolui, Sudipto; Brennan, Daniel; Torrellas, Julia; Wang, Ze; Whyte, John; Diaz-Arrastia, Ramon; Kim, Junghoon J. (NeuroImage clinical, 2023)
•During the first year post-injury, cerebral blood flow (CBF) was decreased in TBI.•CBF worsened overall from 3 to 6 months post-injury in multiple regions.•From 6 to 12 months post-injury, CBF of the right precuneus increased in TBI.•CBF changes in TBI were not explained by concurrent cortical atrophy.•Individual-specific analysis of CBF revealed a relationship with executive function. Traumatic brain injury (TBI) is associated with alterations in cerebral blood flow (CBF), which may underlie functional disability and precipitate TBI-induced neurodegeneration. Although it is known that chronic moderate-severe TBI (msTBI) causes decreases in CBF, the temporal dynamics during the early chronic phase of TBI remain unknown. Using arterial spin labeled (ASL) perfusion magnetic resonance imaging (MRI), we examined longitudinal CBF changes in 29 patients with msTBI at 3, 6, and 12 months post-injury in comparison to 35 demographically-matched healthy controls (HC). We investigated the difference between the two groups and the within-subject time effect in the TBI patients using whole-brain voxel-wise analysis. Mean CBF in gray matter (GM) was lower in the TBI group compared to HC at 6 and 12 months post-injury. Within the TBI group, we identified widespread regional decreases in CBF from 3 to 6 months post-injury. In contrast, there were no regions with decreasing CBF from 6 to 12 months post-injury, indicating stabilization of hypoperfusion. There was instead a small area of increase in CBF observed in the right precuneus. These CBF changes were not accompanied by cortical atrophy. The change in CBF was correlated with change in executive function from 3 to 6 months post-injury in TBI patients, suggesting functional relevance of CBF measures. Understanding the time course of TBI-induced hypoperfusion and its relationship with cognitive improvement could provide an optimal treatment window to benefit long-term outcome.